Coaching Model GROW ME untuk Meningkatkan Kreativitas Guru dalam Kegiatan Mengajar di TK Kristen Petra - Aning Irawati; Hery Winoto; Takim Andriono (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Creativity of PAUD teachers are needed in learning and teaching activities. Teacher competency influences student learning outcomes. PAUD teachers are required to have a set of attitudes, knowledge and skills in increasing stimulation of all aspects of early childhood development. Creativity as the ability to produce meaningful learning. Observation results shows that teacher’s creativity at Petra Christian Kindergarten is low. This research was conducted to determine the application of the GROW ME model coaching method in increasing teacher’s creativity in teaching and learning activities at Petra Christian Kindergarten, Jombang, East Java. This research is a qualitative methods research that refers to the Kemmis and Mctaggart model. The research was conducted in two cycles using the plan-action-observe-reflect stages in each cycle. Research results, the application of the GROW ME coaching model can increase teacher’s creativity in learning and teaching activities at Petra Christian Kindergarten. In the end of first cycle showed results of improvement in 9 research subjects with quite good intensity, an average increase of 12.4%, however, to continue to strengthen the results, another stage was carried out in the second cycle The results of observations in cycle II again showed various and almost even increases in the range of increases among the 9 research subjects. It is necessary to continue providing assistance to strengthen the further results.